(untitled) (International Journal of Physiotherapy, 2019)
Background: Aerobic Exercise is a host of health benefits to reduce vigor risk and maintain body weight. The purpose of the present investigation is to determine the influence of aerobic exercises on body weight and Metabolic Equivalent of Task (MET) activity among cardiac rehabilitation phase II patients. The objective of the study is to investigate the impact of obesity on the efficacy of aerobic capacity. Methods: Fifteen obese (ten males, five females) and fifteen non-obese (eleven males, four females) participants of phase II cardiac rehabilitation were selected from a tertiary care hospital by their Body Mass Index (BMI). They were divided into two groups by simple random technique. Aerobic exercises were given for 12 weeks for post-CABG cardiac rehabilitation phase II obese and non-obese (healthy and overweight) patients. BMI and the Metabolic equivalent of task activity of cardiac rehabilitation phase II patients are measured by enrolling a patient in 12 weeks of aerobic exercises program. Results: The aerobic exercise shows a positive result in both obese and non-obese patients. Aerobic exercises improved metabolic equivalent of task in both obese(4.6667+_0.65134 ;< 0.05) and non-obese patients (4.6923+_.48038 ;< 0.05) significantly.But aerobic exercises were more effective in enhancing the efficacy of aerobic capacity in obese patients. Conclusion: It is evident that aerobic exercises are more effective for obese patients to maintain or reduces weight. Higher MET activity was observed in obese patients.